2003
DOI: 10.1038/sj.tpj.6500157
|View full text |Cite
|
Sign up to set email alerts
|

Role of polymorphic human CYP2B6 in cyclophosphamide bioactivation

Abstract: The role of polymorphic CYP2B6 in cyclophosphamide (CPA) bioactivation was investigated in human liver microsomes. A total of 67 human liver specimens were first genotyped with respect to the CYP2B6*5 and CYP2B6*6 variant alleles. CYP2B6 apoprotein levels in 55 liver microsomal preparations were assessed by immunoblotting. 4-Hydroxy-CPA and hydroxy-bupropion were quantified by using HPLC and LC-MS, respectively. 7-Ethoxy-4-trifluoromethyl coumarin O-deethylase activity was measured fluorometrically. The freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
6
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 24 publications
(34 reference statements)
8
157
6
2
Order By: Relevance
“…CYP2B6 variants have been associated with both decreased (Lang et al, 2001), (Jinno et al, 2003) and unchanged (Xie et al, 2003) protein expression compared with the wild-type gene. Increased specific activity associated with the variants has also been observed (Lang et al, 2001;Jinno et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…CYP2B6 variants have been associated with both decreased (Lang et al, 2001), (Jinno et al, 2003) and unchanged (Xie et al, 2003) protein expression compared with the wild-type gene. Increased specific activity associated with the variants has also been observed (Lang et al, 2001;Jinno et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators identified CYP2B6 16,17 as the major in vitro catalyst of 4-hydroxy CP, others characterized CYP2C9 as low K m hydroxylase, 12,14 and CYP2C19 as high K m hydroxylase, 12,13 but found also that CYP3A4/5 14 was an important enzyme for CP activation. The polymorphic GSTA1, however, contributes to the detoxification of reactive intermediates, therefore GSTA1 could be possibly associated with side effects of CP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 As activation and elimination of CP is mediated by various polymorphic drugmetabolizing enzymes (Figure 1), the question arises whether hereditary polymorphism could modulate the pharmacokinetics of CP. CP is believed to be predominantly activated to 4-hydroxyphosphamide by the polymorphic cytochrome P450 (CYP) enzymes CYP2C9 [12][13][14] and CYP2B6, [15][16][17] but also by CYP2C19 12,13 and CYP3A. 14,15 CYP3A4, CYP3A5 and CYP3A7 contribute to the heterogeneous expression of the human CYP3A family.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide bioactivation was reported to be enhanced in the CYP2B6*6/*6 genotype in vitro and in vivo [85][86][87] . However, contradictory or negative results were presented in other studies of the association between CYP2B6 and pharmacokinetics/clinical outcome [88][89][90][91] .…”
Section: Cyclophosphamidementioning
confidence: 99%